Ventricular diverticulum in Cantrell´s pentalogy: rare but not isolated entities - Rocha-Arrieta, Maria Concepcion (2021)
Pentalogy of Cantrell is a rare entity characterized by a combination of alterations, among which the following stand out: defects of the pericardium, heart, diaphragm, lower third of sternum and abdominal wall. On the other hand, congenital cardiac diverticulum is a rare malformation whose presentation is associated with Cantrell’s pentalogy in some cases. We present the case of a child with Cantrell’s pentalogy who, during follow-up, was diagnosed with left ventricular diverticulum, which required surgical management with a favorable outcome. Addressing these conditions requires the use of cardiovascular images that allow timely decision-making by the treating team.